Preclinical laboratory assessments of predictors of social rank in female cynomolgus monkeys. Issue 4 (18th December 2015) - Kromrey, Sarah A.; Czoty, Paul W.; Nader, Susan H.; Register, Thomas C.; Nader, Michael A.
Abstract : Physiological and behavioral differences between dominant and subordinate monkeys have been useful in preclinical models investigating numerous disease states. In captivity, it has been inferred that subordinate monkeys live in a context of chronic social stress and may be at risk for a variety of dysfunctions; however, the factors that influence eventual rank are not entirely known. The goal of the present study was to first evaluate several phenotypic characteristics as potential trait markers for eventual social rank and then to determine the consequences of social hierarchy on these measures (i.e., state markers). Baseline estradiol, progesterone, cortisol and testosterone concentrations were obtained from 16 pair‐housed female cynomolgus monkeys before and after introduction into new social groups ( n  = 4/group). Furthermore, effects of the initial week of social rank establishment on outcome measures of cognitive performance and homecage activity were examined. Baseline body weight and mean serum estradiol concentrations were the only statistically significant predictors of eventual rank, with future subordinate monkeys weighing less and having higher estradiol concentrations. During initial hierarchy establishment, future subordinate monkeys had increased morning and afternoon cortisol concentrations, increased locomotor activity and impaired cognitive performance on a working memory task. After 3 months of social housing, subordinate monkeys had blunted circulating estradiol and progesterone concentrations. These findings demonstrate differential effects on gonadal hormones and cortisol as a function of social context in normally cycling female monkeys. Furthermore, disruptions in cognitive performance were associated with subordinate status, suggesting strong face validity of this model to the study of factors related to the etiology and treatment of human diseases associated with chronic stress. Am. J. Primatol. 78:402–417, 2016. © 2015 Wiley Periodicals, Inc.